A higher order triangular plate finite element using Airy functions. (November 2020) - Himeur, Mohammed; Guenfoud, Hamza; Guenfoud, Mohamed
The present paper describes the formulation of a new moderately thick plate bending triangular finite element based on Mindlin–Reissner plate theory. It is called a Great Triangular Moderately Thick Plate Finite Element, or GTMTPFE. The formulation is based on the strain approach, on solution of Airy's function and on the analytical integration in the construction of the stiffness matrix. The strengths associated with this approach consist of:  automatic verification of equilibrium conditions and kinematic compatibility conditions,  the enrichment of the degrees of the interpolation polynomials of displacements, strains and constraints (refinement p ),  the consideration distortions sections related to Poisson effects,  the treatment of blocking phenomena related to transverse shear. In general, this approach results in a competitive, robust and efficient new moderately thick plate finite element. This is visible, on the one hand, through its stability against patch tests (constant twists, state of constants moments, transverse shear locking phenomenon, isotropy test). This is visible, through its good response to the patch tests to which it is subjected (constant torsions, state of constant moments, phenomenon of blocking in transverse shears, isotropy test). As has excellent convergence to the reference solution. Thus, it exhibits better performance behavior than other existing plate elements in the literature, particularly for moderately thick plates and for thin plates (L/h ratio greater than 4).